2023
DOI: 10.1186/s41239-022-00369-z
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and factors affecting the adoption of digital games for engineering education: a mixed-method research

Abstract: Digital games are considered relevant in higher education due to their ability to foster authentic, active and experiential learning opportunities that are of importance in engineering education. However, as a relatively new pedagogical tool, there is the need to understand the perceptions of engineering students as well as to identify factors that influence their adoption of games for learning. So far, only a few studies have investigated the perceptions of higher education students towards learning games and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 54 publications
0
10
0
3
Order By: Relevance
“…In this paper, the application of the game‐based assessment framework (GBAF) to the design of assessments for a pre‐existing game is presented. Following the introduction of the GBAF and its application to the design of assessment for a new VR game (Udeozor, Chan, et al., 2023), the current paper shows how the GBAF can be applied to the design of two types of assessments around a pre‐existing game. Using familiar concepts in traditional classroom assessment designs, the GBAF offers a simpler process for designing assessments for educational DGs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this paper, the application of the game‐based assessment framework (GBAF) to the design of assessments for a pre‐existing game is presented. Following the introduction of the GBAF and its application to the design of assessment for a new VR game (Udeozor, Chan, et al., 2023), the current paper shows how the GBAF can be applied to the design of two types of assessments around a pre‐existing game. Using familiar concepts in traditional classroom assessment designs, the GBAF offers a simpler process for designing assessments for educational DGs.…”
Section: Resultsmentioning
confidence: 99%
“…Underpinned by the evidence‐centred design framework (Almond et al., 2003; Mislevy et al., 2003) and the principles of constructive alignment (Biggs, 2003), the GBAF offers a user‐friendly and structured approach to assessment design (for detailed design considerations, cf. Udeozor, Chan, et al., 2023). Designed for educators, the GBAF consists of five components that must be aligned for effective assessment: the overall objectives, learning outcomes, game tasks, scoring metrics and grading methods as shown in Figure 1.…”
Section: Game‐based Assessment Framework (Gbaf)mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, there is a pertinent need to investigate the prevalence of gaming among engineering students, as it has been observed that engagement in video game activities can positively impact student learning outcomes and attitudes (Bodnar et al, 2016). Udeozor et al (2023) also conducted a similar investigation among engineering students, emphasising the significance of studying the relationship between gaming and academic performance. However, it is worth noting that there is a shortage of research examining the perceptions of students, mainly engineering students, in Iran towards gaming.…”
Section: Participantsmentioning
confidence: 99%